PENGARUH TINGKAT PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, UKURAN PEMERINTAH DAERAH, BELANJA MODAL, DAN JUMLAH PENDUDUK TERHADAP KELEMAHAN PENGENDALIAN INTERN PADA PEMERINTAH DAERAH (Studi Empiris Pada Kabupaten Dan Kota Provinsi Riau Dan Sumatera Bara - Iqbal, Muhammad; Tanjung, Amries Rusli; ', Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to analyze of economic growth rate, locally-generated revenue, government size, capital expenditure and population to the weakness of internal control. Object of this research areRiau and Sumatera Barat Province. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined economic growth rate, locally-generated revenue, government size, capital expenditure and population to the weakness of internal control. The results of this research showedeconomic growth rate has an effect tothe weakness of internal control with 0,048 significance, locally-generated revenuehas an effect tothe weakness of internal control with 0,012 significance, government sizehas an effect tothe weakness of internal controlwith 0,009 significance, capital expenditure has no effect tothe weakness of internal control with 0,607 significance and population has an effect tothe weakness of internal control with 0,037 significance The results of this research also showed that coefficient R square is 81,9%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: economic, revenue, government size, capital expenditure and population